INTEGRASI PROSES BISNIS PADA PERUSAHAAN GALANGAN KAPAL PT â€œXYZâ€ SHIPYARD MENGGUNAKAN OPENERP - Dewi, Lily Puspa; Hari S., Yulius; Indahyanti, Uce (Jurnal Informatika, 2014)
In the shipyard industry, ships produced by order and adjust to consumer demand. Business processes that occur at the shipyard company in the shipbuilding process through several stages, ranging from design to delivery. Processes are still done manually so it may cause some difficulty and time. For the solution, system capability is needed to accelerate the business process.  This research considers the OpenERP implementation at PT. XYZ as an application for integrating business processes. The results of this study indicate that OpenERP can answer the problems faced by the business process shipyard company. By using this ERP system offers company integrated system, but success depends on the ERP system implementation strategies are applied. Users can take benefit from the ERP system. The problems of this migration system are on tradition, culture, time and cost.